Experimental investigation on the effect of diameter ratio on two-phase slug flow separation in a T-Junction - Saieed, A. (Elsevier B.V., 2018)
T-junctions are often used in offshore platforms to partially separate gas from produced fluids. Poorly designed T-junctions frequently produce very high liquid (oil and/or water) carryovers, causing major issues to the downstream equipment train which is not designed to handle excessive liquid. This paper reports the liquid carryover experiments in T-junctions using five different side to main arm diameter ratios under slug flow regime. The obtained phase separation curves can be divided into two component variables; liquid-carryover threshold and peak liquid carryover. The experiments demonstrate that with a decrease in diameter ratio both of these variables decrease. Yet, for superior multiphase flow separation, a high liquid carryover threshold and a low peak liquid carryover are required. Hence, the generally accepted rule that a reduction in diameter ratio improves the phase separation is revealed to be an over-extrapolated statement. The novel findings of this work are: 1) for optimum flow splitting under slug flow conditions, the diameter ratio should be kept between 1 and 0.67, while the diameter ratio 0.67 was found to be most suitable; 2) two correlations were developed for predicting two-phase slug flow separation in different diameter ratio T-junctions. These correlations offer beneficial guidance and clarifications for a number of oil and gas flowline and pipeline applications. Â© 2018 Elsevier B.V.